Pengaruh Peletakan Komposisi Warna Monochrome pada Bidang Window Display Terhadap Ketertarikan Pengunjung - Arsaika Widasati (Institut Teknologi Sains Bandung, 2021)
Window display is used to display products, provide information, attract visitors’ attention then persuade visitors to approach and enter the store. Colour composition is the most attractive design element on window display to visitors’ attention the most. This element is the easiest to identified by visitors. Monochromatic colour composition consists of one colour (hue) in various variants of its value and saturation. It is stated as an attractive and effective composition, thus it is widely used in window display spatial elements. This experiment investigated what kind of monochrome compositions that should be applied in window display that attract visitor the most. Window display schematic simulations with monochrome compositions are used as the stimulus of this research. The research subjects observed the simulation while filled out a set of online questionnaires. Results obtained from experiments prove that the monochrome schematic illustration which use a dark color (value 100) on the back wall and on the floor has the highest attractiveness to the visitors among other types of monochrome compositions.